Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s10142-018-0610-3
|View full text |Cite
|
Sign up to set email alerts
|

Searching whole genome sequences for biochemical identification features of emerging and reemerging pathogenic Corynebacterium species

Abstract: Biochemical tests are traditionally used for bacterial identification at the species level in clinical microbiology laboratories. While biochemical profiles are generally efficient for the identification of the most important corynebacterial pathogen Corynebacterium diphtheriae, their ability to differentiate between biovars of this bacterium is still controversial. Besides, the unambiguous identification of emerging human pathogenic species of the genus Corynebacterium may be hampered by highly variable bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 80 publications
2
14
1
Order By: Relevance
“…Our genome-wide association study (GWAS) of accessory genes with the biovar phenotype revealed a strong association of a cluster of genes that includes spuA (DIP357; Additional file 4: Fig. S7) with biovar Gravis isolates, providing statistical support to the discovery of Santos et al [62]. This association was stronger within the Gravis lineage; in contrast within the Mitis lineage, few (5 out of 17) of the biovar Gravis isolates possessed spuA (Fig.…”
Section: Genetic Events Linked To Biovar Statussupporting
confidence: 70%
See 3 more Smart Citations
“…Our genome-wide association study (GWAS) of accessory genes with the biovar phenotype revealed a strong association of a cluster of genes that includes spuA (DIP357; Additional file 4: Fig. S7) with biovar Gravis isolates, providing statistical support to the discovery of Santos et al [62]. This association was stronger within the Gravis lineage; in contrast within the Mitis lineage, few (5 out of 17) of the biovar Gravis isolates possessed spuA (Fig.…”
Section: Genetic Events Linked To Biovar Statussupporting
confidence: 70%
“…The nitrate reductase activity differentiates Mitis and Gravis isolates, which are positive, from Belfanti isolates, which are nitrate-negative. We found that the nitrate reduction narKGHJI gene cluster [62] was disrupted in three of the six isolates assigned to the biovar Belfanti: strains FRC0480 and FRC0481 had a G to A mutation at position 675 of the narG gene, leading to a stop codon, whereas in strain CIPA99, approximately 100 nucleotides were inserted at position 446 in narG. No molecular explanation was found for the lack of nitrate reductase ability of the three other Belfanti strains when scrutinizing the narKGHJI gene cluster and adjacent molybdenum cofactor biosynthesis genes [63].…”
Section: Genetic Events Linked To Biovar Statusmentioning
confidence: 85%
See 2 more Smart Citations
“…Traditionally, these microorganisms have been routinely identified by biochemical tests using the API Coryne system (bioMérieux, Craponne, France) or the RapID CB PLUS system (Thermo Fisher Scientific, Waltham, MA, USA) in clinical microbiology laboratories [11,12]. However, these methods have low sensitivity, and are timeconsuming and unreliable for species identification, especially in the case of C. simulans, due to its similarities with C. striatum [13,14].…”
Section: Introductionmentioning
confidence: 99%